Heart rate based on electrocardiography (ECG) and its relationship with systolic blood pressure - Siti Nurasma Jalaludin, 1987-; Nasrul Humaimi Mahmood; Fakulti Kejuruteraan Elektrik (2010)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik Perubatan)) - Universiti Teknologi Malaysia, 2010